2015
DOI: 10.3846/13923730.2014.945950
|View full text |Cite
|
Sign up to set email alerts
|

Use of Value Management Workshops and Critical. Success Factors in Introducing Local Experience on The. International Construction Projects

Abstract: Critical success factors can be used in value management workshops to determine the client value system, which in turn is critically important to the briefing process and the successful delivery of construction projects. This research is concerned with international construction projects. In particular, it investigates the impact of local knowledge on the client value system. Workshops were organised on 12 international projects in the western Balkans region. The initial client value system was captured by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…In addition, the findings have shown resistance in the implementation of value management practices in the construction industry as well as some influencing factors that allow the implementation of value management in the construction industry. The findings are in-line with the findings of Surlan et al, [18] who indicated the implications of value management workshops and critical success factors in instigating local experience on the international construction projects. The study has supported the findings of the current study that there is an immediate need for increasing the awareness of value management among stakeholders.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the findings have shown resistance in the implementation of value management practices in the construction industry as well as some influencing factors that allow the implementation of value management in the construction industry. The findings are in-line with the findings of Surlan et al, [18] who indicated the implications of value management workshops and critical success factors in instigating local experience on the international construction projects. The study has supported the findings of the current study that there is an immediate need for increasing the awareness of value management among stakeholders.…”
Section: Discussionsupporting
confidence: 90%
“…• Problem of reflecting the deferred taxes; Other features of accounting and taxation. 6. Financial indicators calculated based on accounting (financial) statements depend on the company's accounting policy.…”
Section: Resultsmentioning
confidence: 99%
“…However, data on the company's value should be obtained by the management as part of management accounting, since management requires information on the company's value. Among other things, this is necessary to understand the conditions required to achieve the necessary investments [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, Value Methodology is used as the fulfilment of a formal obligation, but does not result in considerable benefit due to the low effort exerted by experts [13,14]. However, in countries where the application of VM is not mandatory, market actors call for a government measure to make the methodology obligatory as part of the local construction process [15,16,17].…”
Section: About Value Methodologymentioning
confidence: 99%